Nutritional profile and food habits of Military Police (Research, Society and Development, 2021)
The causes of the growing number of cases of overweight and obesity are multifactorial, among which we can mention genetic factors, age; environmental, emotional and occupational issues; and unfavorable changes in diet and physical activity; that can act alone or together. This study aimed to assess the nutritional profile and eating habits of military police in the city of Uberaba / MG. Data collection was carried out with 117 military personnel, of both sexes, on an administrative and operational scale. Self-administered forms containing information on the following variables were used: socioeconomic data, clinical characteristics, physical activity, anthropometric data and habits questionnaire. The nutritional profile was evaluated according to the classification ranges of the Body Mass Index (BMI) and Waist circumference (WC) for adults, according to the parameters proposed by the World Health Organization. A high frequency of overweight was observed (68% ) among the military police officers evaluated and abdominal obesity with a higher prevalence among males (71.83%). A positive correlation was observed between BMI and WC. In the distribution of food frequency, the vast majority presented a low consumption of nutritionally adequate foods. Insufficient physical activity and unbalanced diet were found, which need care and guidance.